Clinical validation of the nursing diagnostic proposition perioperative thirst (Revista Latino-Americana de Enfermagem, 2023)
Objective: to verify the clinical validity of the proposition of a new nursing diagnosis called perioperative thirst, based on the diagnostic accuracy of its clinical indicators, including the magnitude of effect of its etiological factors. Method: clinical diagnostic validation study with a total of 150 surgical patients at a university hospital. Sociodemographic variables and clinical indicators related to thirst were collected. The latent class analysis technique was used. Results: two models of latent classes were proposed for the defining characteristics. The model adjusted preoperatively included: dry lips, thick saliva, thick tongue, desire to drink water, caregiver report, dry throat and constant swallowing of saliva. In the postoperative period: dry throat, thick saliva, thick tongue, constant swallowing of saliva, desire to drink water, bad taste in the mouth. The factors related to “high ambient temperature” and “dry mouth” are associated with the presence of thirst, as well as the associated conditions “use of anticholinergics” and “intubation”. The prevalence of thirst was 62.6% in the pre and 50.2% in the immediate postoperative period. Conclusion: the diagnostic proposition of perioperative thirst showed good accuracy parameters for its clinical indicators and etiological effects. This proposition in a nursing taxonomy will allow greater visibility, appreciation and treatment of this symptom.